RANCANGAN APLIKASI SMS GATEWAY UNTUK MENINGKATKAN PELAYANAN KEPADA PASIEN DI RUMAH SAKIT IBNU SINA MAKASSAR - Sahabuddin (P3M STMIK Profesional Makassar, 2016)
Rumah Sakit Ibnu Sina Makassar is a large hospital that gives the servicing to patients. To increase servicing, the patient can registry through SMS Gateway. Through a program SMS calls